Approach of pulmonologists in Turkey to noninvasive mechanical ventilation use at home for chronic respiratory failure - Ozsancak Ugurlu, Aylin; Berk Takir, Huriye; Ergan, Begum; In, Erdal; Ozyilmaz, Ezgi; Ertan Edipoglu, Ozlem; Karakurt, Zuhal (Turkish Assoc Tuberculosis & Thorax, 2016)
Introduction: To define approach of pulmonologists in Turkey to noninvasive mechanical ventilation ( NIV) use for chronic respiratory failure ( CRF), the most currently applied technique for home mechanical ventilation. Patients and Methods: A 38-question survey, developed and tested by the authors, was distributed throughout Turkey to 2205 pulmonologists by e-mail. Results: Twenty-seven percent of the pulmonologists responded ( n= 596). Domiciliary NIV was reported to be prescribed by 340 physicians [ 57.1% of all responders and 81% of pulmonologists practicing NIV at clinical practice ( n= 420)]. NIV prescription was associated with physician's title, type of hospital, duration of medical license, total number of patients treated with NIV during residency and current number of patients treated with NIV per week ( p< 0.05). Main estimated indications were listed as chronic obstructive pulmonary disease ( median, 25-75 percentile of the prescriptions: 75%, 60-85), obesity hypoventilation syndrome ( 10%, 2-15), overlap syndrome ( 10%, 0-20) and restrictive lung disease ( 5%, 2-10). For utilization of NIV at home, Bilevel positive airway pressure-spontaneous mode ( 40%, 0-80) and oronasal mask ( 90%, 60-100) were stated as the most frequently recommended mode and interface, respectively. Pressure settings were most often titrated based on arterial blood gas findings ( 79.2%). Humidifier was stated not to be prescribed by approximately half of the physicians recommending domicilliary NIV, and the main reason for this ( 59.2%) was being un-refundable by social security foundation. Conclusion: There is a wide variation in Turkey for prescription of NIV, which is supposed to improve clinical course of patients with CRF. Further studies are required to determine the possible causes of these differences, frequency of use and patient outcomes in this setting.
Türkiye'de kronik solunum yetmezliğinde evde noninvaziv mekanik ventilasyon kullanımına göğüs hastalıkları doktorlarının yaklaşımı
Keywords: Noninvasive ventilation; chronic respiratory failure; survey; chronic obstructive pulmonary disease